(3GdahGFO GdNGbGfjI GdCMeOjIs - (3GdTQhGfj , eMeO Gejf Hf UOQGdOjf GdTQhGfj,J (B1036 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd eMeO Cejf Hf UOQ GdedI hGdOjf GdTQhGfi bO fHZJ ajgG bOjekG hUHZJ HgG COjekG s
(3BNQgG (B:s
(3CeQ XgQ ai edcg jLH Ydi CQcGf OhdJg hdjcf gPG BNQ eG CQOfG EjQGOg ef OQQ GdahGFO hZQQ GdaQGFO JeJ GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B73s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs